Correction of oxidative stress enhances enzyme replacement therapy in Pompe disease - Antonietta Tarallo; Carla Damiano; Sandra Strollo; Nadia Minopoli; Alessia Indrieri; Elena Polishchuk; Francesca Zappa; Edoardo Nusco; Simona Fecarotta; Caterina Porto; Marcella Coletta; Roberta Iacono; et al. (EMBO Molecular Medicine)
Abstract Pompe disease is a metabolic myopathy due to acid alpha‐glucosidase deficiency. In addition to glycogen storage, secondary dysregulation of cellular functions, such as autophagy and oxidative stress, contributes to the disease pathophysiology. We have tested whether oxidative stress impacts on enzyme replacement therapy with recombinant human alpha‐glucosidase (rhGAA), currently the standard of care for Pompe disease patients, and whether correction of oxidative stress may be beneficial for rhGAA therapy. We found elevated oxidative stress levels in tissues from the Pompe disease murine model and in patients’ cells. In cells, stress levels inversely correlated with the ability of rhGAA to correct the enzymatic deficiency. Antioxidants (N‐acetylcysteine, idebenone, resveratrol, edaravone) improved alpha‐glucosidase activity in rhGAA‐treated cells, enhanced enzyme processing, and improved mannose‐6‐phosphate receptor localization. When co‐administered with rhGAA, antioxidants improved alpha‐glucosidase activity in tissues from the Pompe disease mouse model. These results indicate that oxidative stress impacts on the efficacy of enzyme replacement therapy in Pompe disease and that manipulation of secondary abnormalities may represent a strategy to improve the efficacy of therapies for this disorder.